The role of seed germination in the invasion process of Honey locust (Gleditsia triacanthos L., Fabaceae): comparison with a native confamilial - Ferreras, Ana Elisa (2015)
Identifying plant traits that promote invasiveness has been a major goal in invasion ecology. Germination plays a central role in plant life cycle and could therefore be a key trait in determining species invasiveness. In this study, seed germination of two confamilial, co-occurring species that share ecological characteristics, the exotic invasive Gleditsia triacanthos L. and the native Acacia aroma Gillies ex. Hook. & Arn., was compared. Seeds were obtained from individuals of three localities in the Chaco Serrano region of Córdoba, Argentina. Percentage of seed germination and mean germination time were recorded in chemically and mechanically scarified seeds, and the former variable was also recorded in seeds subjected to: passage through the digestive tract of dispersers, fire simulations, fire simulation plus mechanical scarification, seed longevity, and dormancy break over time. In general, both species showed similar germination percentage. However, non-scarified seeds of the exotic species lost physical dormancy when subjected to experiments of dormancy break over time, whereas, the native species had shorter mean germination time. The greater percentage of seed germination over time of the exotic species than of the native one might be triggering the spread of the former, whereas the shorter mean germination time might be hindering its expansion to more arid regions. The study of different mechanisms for achieving seed germination, particularly in hard seed species, could provide important information on the expansion of invasive species as well as useful knowledge for their management.